Watson and DNA : making a scientific revolution - McElheny, Victor K. (Cambridge, MA : Perseus, 2003)
From the discovery of the double helix to the imminent sequencing of the human genome, James Watson has been at dead center in this great biological revolution. Since the very morning after his Nobel Prize-winning discovery, he has continued to ride the scientific supernova that he and his collaborator, Francis Crick, detonated in 1953. Targeting the big questions, mobilizing the best talent, writing the textbook that defined molecular biology, energizing the "war on cancer," he has served as a prime mover of the DNA era. Now, a distinguished science reporter who has known him for decades and worked for him for four years, with unique access to the scientists who know Watson best, has written an unauthorized, non-reverential account of this extraordinary man. While Watson is probably the most influential scientist in the last half-century, he is also one of the most controversial. From the ruthless competition in the race to identify the structure of DNA, to clashes with ethicists over charged issues in genetics, to a chorus of Bronx cheers for his recent memoir, Watson has left a wake of detractors as well as fans. Until now, Watson has managed to keep control over his legend, fending off aspiring biographers with his own memoirs. Victor McElheny gets behind this invented persona, bringing us close to the relentless genius who triggered and sustained a revolution in science that affects us all.
"A Merloyd Lawrence book."
Includes bibliographical references (p. 289-345) and index.
Keywords: Watson, James D., -- 1928-; Molecular biology -- United States -- Biography; Molecular biologists -- United States -- Biography; Molecular genetics; Genetics -- United States -- Biography; Biology -- Molecular genetics -- Biography; DNA -- United States -- Biography; Genomes -- United States -- Biography